2009
DOI: 10.1007/s11240-009-9508-z
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis and plant regeneration of northern red oak (Quercus rubra L.)

Abstract: A somatic embryogenesis protocol for plant regeneration of northern red oak (Quercus rubra) was established from immature cotyledon explants. Embryogenic callus cultures were induced on Murashige and Skoog medium (MS) containing 3% sucrose, 0.24% Phytagel TM , and various concentrations of 2,4-dichlorophenoxyacetic acid (2,4-D) after 4 weeks of culture in darkness. A higher response (66%) of embryogenic callus was induced on 0.45 lM 2,4-D. Higher numbers of globular-(31), heart-(17), torpedo-(12), and cotyledo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Although a relatively high embryogenic response was achieved after continuous culture in M1 medium (Procedure 4), histodifferentiation of somatic embryos to the cotyledonary-stage was inhibited, suggesting that PGR-free medium promoted the development of somatic embryos. In accordance with the present results, initiation of embryogenic cultures from immature zygotic embryos of several other Quercus species was achieved by successive use of two culture media--induction medium and expression medium with or without auxin supplement (Chalupa 1993;Kim et al 1997;Toribio et al 2005;Vengadesan and Pijut 2009). However, in the few embryogenic systems established from mature oak explants, the use of a three successive culture media, similar to the standard procedure defined in white oak, has been reported in studies on SE induction from male catkins of Q. bicolor (Gingas 1991), leaf explants of Q. suber (Hernández et al 2003;Toribio et al 2005) and shoot apex and leaf explants of Q. robur (Valladares et al 2006;San-José et al 2010).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although a relatively high embryogenic response was achieved after continuous culture in M1 medium (Procedure 4), histodifferentiation of somatic embryos to the cotyledonary-stage was inhibited, suggesting that PGR-free medium promoted the development of somatic embryos. In accordance with the present results, initiation of embryogenic cultures from immature zygotic embryos of several other Quercus species was achieved by successive use of two culture media--induction medium and expression medium with or without auxin supplement (Chalupa 1993;Kim et al 1997;Toribio et al 2005;Vengadesan and Pijut 2009). However, in the few embryogenic systems established from mature oak explants, the use of a three successive culture media, similar to the standard procedure defined in white oak, has been reported in studies on SE induction from male catkins of Q. bicolor (Gingas 1991), leaf explants of Q. suber (Hernández et al 2003;Toribio et al 2005) and shoot apex and leaf explants of Q. robur (Valladares et al 2006;San-José et al 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Great progress has been made in developing embryogenic systems for European oaks, including Q. suber and Q. robur, in which initiation of embryogenic cultures from mature trees has been achieved by use of leaf explants excised from epicormic shoots forced from branch segments (Hernández et al 2003;Toribio et al 2004), and from leaf explants and shoot apices excised from shoot cultures of Q. robur of mature origin (San-José et al 2010). Unfortunately, studies of SE in American oaks are scarce and limited to initiation of somatic embryos from immature zygotic embryos (Gingas and Lineberger 1989;Vengadesan and Pijut 2009) and leaf discs from seedlings (Rancillac et al 1996) of Q. rubra. When male catkins were used as explants, embryogenic cultures were obtained from Q. bicolor, whereas the callus formed in Q. rubra degenerated after 5 months in culture, and failed to yield embryogenic structures (Gingas 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Explants were cultured on MS or WPM media with addition of 0.5 mg l -1 2,4-D and 0.1-1.0 mg l -1 BA in darkness. Another type of explants used for successful induction of somatic embryogenesis of Q. rubra were immature cotyledons excised from acorns gathered in mid-July (Vengadesan and Pijut 2009). Immature cotyledon explants produced embryogenic callus when cultured on MS medium supplemented with various concentrations of 2,4-D in darkness.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, among broadleaved trees, most attention was paid to oaks (Quercus spp.) (Joergensen 1988;Gingas and Lineberger 1989;Chmielarz 1999;Wilhelm 2000;Valladares et al 2006;Corredoira et al 2006;Vengadesan and Pijut 2009;references in Lelu-Walter et al 2011;Blasco et al 2013). In contrast, research on the application of this method in the micropropagation of Fagus is scarce (Chalupa 1987;Joergensen 1988;Vieitez et al 1992;Dujičkova and Mala 1995;Naujoks 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Plants in this stage are then ready for acclimatization (Pires et al, 2003;Figure 2a As reported above, somatic embryogenesis is a regeneration strategy with enormous potential for breeding programs. Somatic embryos were developed in Q. canariensis (Bueno et al, 1996;, Q. rubra (Vengadesan & Pijut, 2009), Q. serrata Takur et al, 1999), Q. robur (Cuenca et al, 1998;Endemann et al, 2002;Wilhelm et al, 1999), Q. acutissima (e.g., Kim, 2000) and Q. petrea (Chalupa, 2005). However, not only most studies use juvenile sources of explants (e.g., zygotic embryos and seedlings), but also plant conversion frequencies are still low, supporting the recalcitrance of these species.…”
Section: Quercus Suber In Vitro Cloning: a Reliable Protocol?mentioning
confidence: 99%